Estimating the social carbon costs from power and desalination productions in UAE. (October 2019) - Saleh, Layla; Zaabi, Mohamed al; Mezher, Toufic
Abstract: Climate change has become one of the most pervasive issues of our time, its consequences are not only affecting the natural environment but the economic development as well. Greenhouse gases, especially CO2, emitted from power plants are one of the most challenging problems facing societies. Estimating the real cost of such emissions should include both internal and external costs that include the social cost of carbon (SCC). SCC is usually estimated as the net present value of the climate change effects over the next 100 years of one ton of carbon dioxide emitted to the atmosphere today. The United Arab Emirates (UAE) has one of the highest per capita rates of power and water consumptions in the world which are leading to a large amount of CO2 and other greenhouse gas emissions. The majority of the water production in the country comes from desalination plants that are energy intensive, hence the link between energy and water (the nexus). Thermal desalination technologies are the major techniques used in UAE, therefore, cogeneration-based power plants dominate the energy sector in the UAE. This nexus is resulting in a significant impact on the environment due to GHG emissions, as well as other solid and liquid wastes. This paper investigates the potential SCC in UAE from the year 2010 until the year 2030. Additionally, different mitigation strategies were analyzed to reduce SCC by including energy mix from conventional and non-conventional sources. It is estimated that by 2030 the total CO2 emissions will be around 139.252 billion tons from power generation and 18.8 million tons from water productions. SCC is estimated to be around 6.96 trillion dollars and 938.4 million dollars for energy and water productions respectively. With the implementation of mitigation strategies, the SCC can be reduced by 1.5 trillion dollars by the year 2030. Highlights: Environmental, social and economic consequences of climate change. Pollution and CO2 emissions from power and desalination technologies. The linkages between energy and water in UAE, hence the Water-Energy Nexus. Estimating the Social Cost of Carbon (SCC) for UAE between the years 2010–2030.